Food allergy and atopic dermatitis as trigger factors of severe and long-term rotavirus diarrhea in early-aged children - Vorobiova, N. V.; Воробйова, Наталія Володимирівна (НУОЗ ім. П. Л. Шупика, 2022)
Objective. To evaluate the effect of concomitant food allergy (FA) and atopic dermatitis (AD) on the severity and duration of the diarrheal syndrome in rotavirus infection (RVI) in early-aged children.
Харчова алергія та атопічний дерматит як тригерні фактори тяжкої та тривалої ротавірусної діареї у дітей раннього віку
ORCID: 0000-0001-7610-8067